1983
DOI: 10.1192/bjp.142.1.47
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Auditory Hallucinations and Spontaneous Fluctuations of Skin Conductance in Schizophrenia

Abstract: A sample was collected of schizophrenic patients exhibiting nonverbal signs of intermittent auditory hallucinations. A video-tape record was made for each of a session, during which the patient's skin conductance was monitored. Independent raters achieved reasonable agreement on the onset of periods of hallucinatory activity, as judged from non-verbal signs. The skin conductance tracing was scored independently for spontaneous fluctuations. In the 10 patients with satisfactory records the onset of hallucinator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

1985
1985
2002
2002

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 8 publications
2
18
0
2
Order By: Relevance
“…Recent research has demonstrated orderly relationships between hallucinations and stress-induced arousal (e.g. Cooklin, Sturgeon & Leff, 1983), environmental stimulation (e.g. Margo, Hemsley & Slade, 1981 ;Slade, 1974), and various cognitive variables (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has demonstrated orderly relationships between hallucinations and stress-induced arousal (e.g. Cooklin, Sturgeon & Leff, 1983), environmental stimulation (e.g. Margo, Hemsley & Slade, 1981 ;Slade, 1974), and various cognitive variables (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There is an association between stress experienced and frequency of intrusive thoughts (Horowitz, 1975) and it has been found that stress and arousal are associated with an increase in auditory hallucinations (Slade, 1972;Cooklin, Sturgeon and Leff, 1983).…”
Section: Common Determinants Of Intrusive Thoughts and Auditory Hallumentioning
confidence: 99%
“…The role of anxiety, and therefore, arousal in the presence of psychotic symptoms is starting to be more generally recognized. Morrison (1998) looks at the role of arousal, triggered by negative attribution, in maintaining symptoms, and cites Allen and Argus, (1968) and Cooklin et al (1983) as studies linking psychophysiological arousal with onset of hallucinatory episodes. Tarrier and Turpin (1992) describe the role of arousal in relapse using psychophysiological data.…”
Section: Clarkementioning
confidence: 99%